A universal route with fine kinetic control to a family of penta-twinned gold nanocrystals. Issue 38 (31st August 2021) - Zhang, Tao; Li, Xuejiao; Sun, Yiqiang; Liu, Dilong; Li, Cuncheng; Cai, Weiping; Li, Yue
Abstract : We report the synthesis of linear ADPr oligomers of defined length up to a pentamer using an improved solid phase method. Binding study with human oncogenic helicase ALC1 shows that ADPr oligomers bind to ALC1 in a length-dependent manner. Abstract : Some of the major difficulties hindering the synthesis of different types of colloidal nanocrystals are their complex synthetic methods and the lack of a universal growth mechanism in one system. Herein, we propose a general strategy of kinetically controlled seed-mediated growth to synthesize a family of penta-twinned gold nanocrystals. Specifically, different kinds of penta-twinned nanocrystals (truncated penta-twinned decahedra, truncated bipyramids, bipyramids, truncated bipyramids with tips, star-like penta-twinned nanocrystals, decahedra with concave edges, and decahedra) with tunable sizes and high purity were readily achieved in one system solely by tailoring the deposition kinetics of adatoms on different sites of decahedral seeds. The controllable deposition kinetics can be realized by changing the ratio of reductant/gold precursors ( R ), which dictates whether horizontal or vertical features along the 5-fold axis direction of Au decahedral seeds are produced. Additionally, the selective growth of a second metal (silver) on penta-twinned gold seeds can be reached through minor modification of R, which opens a new avenue for mechanistic investigation by visualizing the seed localization within the final particles. The present work demonstrates a general paradigm for the kinetic growth of penta-twinned crystals and would be extended to the synthesis of other families of nanocrystals.